2021
DOI: 10.1038/s41598-021-81031-y
|View full text |Cite|
|
Sign up to set email alerts
|

Implicit motor learning within three trials

Abstract: In motor learning, the slow development of implicit learning is traditionally taken for granted. While much is known about training performance during adaptation to a perturbation in reaches, saccades and locomotion, little is known about the time course of the underlying implicit processes during normal motor adaptation. Implicit learning is characterized by both changes in internal models and state estimates of limb position. Here, we measure both as reach aftereffects and shifts in hand localization in our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
62
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(77 citation statements)
references
References 43 publications
13
62
2
Order By: Relevance
“…In some models, proprioception is seen as playing a passive role, a signal that is biased by vision but does not drive implicit adaptation (Mattar et al, 2013; Ohashi, Gribble, et al, 2019; Ohashi, Valle-Mena, et al, 2019). Other models consider a contribution of proprioception to implicit adaptation, but the computational principles of how this information is used have not been elucidated (Rossi et al, 2021; Ruttle et al, 2021; Salomonczyk et al, 2013; Zbib et al, 2016). In this paper, we present a new model in which proprioception is the primary driver of implicit adaptation.…”
Section: The Neglected Role Of Proprioceptionmentioning
confidence: 99%
See 1 more Smart Citation
“…In some models, proprioception is seen as playing a passive role, a signal that is biased by vision but does not drive implicit adaptation (Mattar et al, 2013; Ohashi, Gribble, et al, 2019; Ohashi, Valle-Mena, et al, 2019). Other models consider a contribution of proprioception to implicit adaptation, but the computational principles of how this information is used have not been elucidated (Rossi et al, 2021; Ruttle et al, 2021; Salomonczyk et al, 2013; Zbib et al, 2016). In this paper, we present a new model in which proprioception is the primary driver of implicit adaptation.…”
Section: The Neglected Role Of Proprioceptionmentioning
confidence: 99%
“…Similarly, a proprioceptive shift is observed when participants locate their unseen hand using a touch screen (Cressman & Henriques, 2010). Second, these shifts occur rapidly (Ruttle et al, 2016, 2021, 2018), with both the visual and proprioceptive shift reaching asymptotic values within just a few reaches after the introduction of a visuomotor perturbation (Ruttle et al, 2016). In the following section, we formalize how sensory recalibration during visuomotor adaptation drives implicit adaptation.…”
Section: Interaction Of Visual and Proprioceptive Informationmentioning
confidence: 99%
“…The predictive forward model can be trained by comparing predicted and actual sensory feedback and using the resulting error signal to make increasingly more accurate predictions. It has been demonstrated that such internal perception-action loops are relevant for implicit motor and perceptual sequence learning (Janacsek et al, 2020;Lutz et al, 2018;Ruttle et al, 2021;Ziessler Nattkemper, 2001). Both theoretical viewpoints, the Unexpected Event Hypothesis and the Radical Plasticity Hypothesis state that it is not these implicit internal models themselves that are consciously accessible.…”
Section: Metacognitive Learning Mechanisms and Unexpected Eventsmentioning
confidence: 99%
“…For instance, observers are more accurate when tracking and predicting simulated fly balls that move with natural gravity compared to balls that do not (0g), or that are unnaturally impacted by gravity (2g; Delle Monache et al, 2019;Bosco et al, 2012). Moreover, humans are generally able to quickly adapt movements after only a few trial repetitions (Ruttle et al, 2021). For example, improvements in the ability to manually intercept (Brenner et al, 2016) and predictively pursue (Bennett & Barnes, 2006) accelerating targets after a few (eight to twelve) repetitions of the same acceleration rate have been reported.…”
Section: Assessing Model Predictions Of Accelerating Motion Integrationmentioning
confidence: 99%